Rising Incidence of Sporothrix brasiliensis Infections, Curitiba, Brazil, 2011-2022 (2023)
Zoonotic outbreaks of sporotrichosis are increasing in Brazil. We examined and described the emergence of cat-transmitted sporotrichosis (CTS) caused by the fungal pathogen Sporothrix brasiliensis. We calculated incidence and mapped geographic distribution of cases in Curitiba, Brazil, by reviewing medical records from 216 sporotrichosis cases diagnosed during 2011–May 2022. Proven sporotrichosis was established in 84 (39%) patients and probable sporotrichosis in 132 (61%). Incidence increased from 0.3 cases/100,000 outpatient visit-years in 2011 to 21.4 cases/100,000 outpatient visit-years in 2021; of the 216 cases, 58% (n = 126) were diagnosed during 2019–2021. The main clinical form of sporotrichosis was lymphocutaneous (63%), followed by localized cutaneous (24%), ocular (10%), multisite infections (3%), and cutaneous disseminated (0.5%). Since the first report of CTS in Curitiba in 2011, sporotrichosis has increased substantially, indicating continuous disease transmission. Clinician and public awareness of CTS and efforts to prevent transmission are needed.